Influence of playing standard on the physical demands of professional rugby league - Gabbett, T. C. (Journal of Sports Sciences, 2013)
In this paper we report on two studies that investigated the physical demands of professional rugby league match-play. Instudy one, National Rugby League (NRL) and National Youth Competition (NYC) players underwent global positioning system (GPS) analysis during competitive matches. No differences (P > 0.05) were observed between playing standards for minutes played, total distance covered, or the distances covered at low and high speeds. However, NRL players engaged in significantly more repeated high-intensity effort bouts than NYC players (13.1 ± 0.8 bouts vs. 9.7 ± 1.1 bouts). Reductions in physical performance occurred from the first to second half for both NRL and NYC players. In study two, we investigated, in the same players, the physical demands of professional rugby league match-play when players were competing in trial and regular fixture matches. The locomotor demands of trial matches were lower than fixture matches, with players covering less distance per minute of match-play, including less distance at low and high speeds. Players were also less likely to engage in repeated high-intensity effort bouts in trial matches than fixtures. These findings demonstrate that neither NYC matches nor NRL trial matches adequately reflect the intense physical demands of NRL fixture matches.